A comparative study of a stalker typology: An analysis of the stalking case files of the Ontario Provincial Police. - Maksymchuk, Lesa. (University of Ottawa (Canada), 2001)
In 1993, the Los Angeles Police Department, with the assistance of mental health professionals, constructed a stalker typology in order to understand the elements of stalking and implement an organizational paradigm for the management of these incidents (Zona, Sharma and Lane, 1993). The purpose of this study is to assess the relevance of this typology in a Canadian context. This research study conducts a Chi-square analysis on 152 stalking case files obtained from the O.P.P. Threat Assessment Unit. The results indicate that the majority of the Ontario stalking cases were consistent with the Zona typology. For the most part, the same variables found significant in the initial study were also significant in this study. However, there were a larger number of simple obsessional stalkers. It is this group that poses the greatest threat of violence to their victims, and this result emphasizes the need for early intervention and prevention on the part of the police. (Abstract shortened by UMI.)
Keywords: Psychology, Personality.